A new higher-order RBF-FD scheme with optimal variable shape parameter for partial differential equation - Ng Y.L.; Ng K.C.; Sheu T.W.H. (Taylor and Francis Ltd., 2023)
Cost effectiveness; Finite difference method; Iterative methods; Partial differential equations; Computational costs; Optimal variables; Partial differential equations (PDE); Polynomial form; Radial basis functions; Rate of convergence; Shape parameters; Solution accuracy; Radial basis function networks